2‐Hydroxyethyl methacrylate inflammatory effects in human gingival fibroblasts. (9th November 2012) - Di Nisio, C.; Zara, S.; Cataldi, A.; di Giacomo, V.
Abstract Aim To investigate the inflammatory response in human gingival fibroblasts (HGFs) treated with a relatively low 2‐hydroxyethyl methacrylate (HEMA) concentration by studying reactive oxygen species (ROS) production, cyclooxygenase‐2 (COX‐2) and tumour necrosis factor‐alpha (TNF‐α) gene expression, and prostaglandin E2 (PGE2) release. Methodology Cultured HGFs were exposed to 3 mmol L−1 HEMA for 0, 24 or 96 h. ROS production was investigated by flow cytometry; TNF‐α and COX‐2 gene expression was determined by RT‐PCR, and prostaglandin E2 production was detected by an enzyme immunoassay. Results After 24‐ or 96‐h HEMA incubation, ROS levels were approximately eightfold and elevenfold higher than controls, whilst COX‐2 gene expression was approximately twofold or fourfold higher than controls, respectively. Twenty‐four‐hour exposure enhanced TNF‐α mRNA levels by approximately 66%, whilst after 96‐h incubation, TNF‐α gene expression was fivefold higher than controls. Ninety‐six‐hour HEMA treatment increased PGE2 concentration in the culture medium by around 17% compared with controls. Conclusions 2‐Hydroxyethyl methacrylate treatment (3 mmol L−1) induced an inflammatory response in HGFs modulated by ROS production, as well as by the increase in TNF‐α and COX‐2 gene expression and by PGE2 release.